Study on Manufacturing Environmentally Friendly Alkyd Paint - Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 1DO - 10.25073/2588-1140/vnunst.4954, 2021)
The article presents results of studying and manufacturing environmentally friendly alkyd paint. By producing a polysaccharide intermediate emulsion (LPR), about 20% of water to total paint volume was added. Mechanical properties (impact resistance, flexural strength, adhesion) of paint films were studied. In addition, the paper presents results of thermal stability, 10-cycle UV-thermo-humidity complex stability of paint film. Ability of films to withstand 03-cycle heat shocking of films at temperatures of + 50 o C and -50 o C was investigated. The properties of studying paint were compared with those of an alkyd paint of Hanoi Synthetic Paint Company. Results show that the environmentally friendly alkyd paint has less volatile organic compounds (VOC), uses a smaller amount of toxic solvents, while its properties are comparable to common alkyd paint.